ORIENTASI PASAR, SOSIAL MEDIA DAN KOMPETENSI PENGETAHUAN DALAM MENINGKAKTKAN KINERJA UMKM (STUDI PADA PELAKU UMKM DI KOTA WAINGAPU) - Bunang, Yani Pindi; Situmorang, Tumpal P. (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This study aims to explore the factors that drive the performance of MSMEs in Waingapu City. This study investigates the relationship between Social Media, Market Orientation, and Knowledge Competency and MSME performance. The respondents were MSMEs in the food and service sector in Waingapu City, with a total of 100 people. The analysis was carried out through validity, probability, classical, descriptive, and multiple linear assumption tests, using SPSS 21. Regression analysis shows that Social Media has a negative influence, while Market Orientation and Knowledge Competency have a positive influence on the performance of MSMEs. These findings provide insight into the factors that affect MSME performance, which can be used as a basis for the development of strategies and policies that support the growth of the MSME sector.